Effects of specific COX-2-inhibition on renin release and renal and systemic prostanoid synthesis in healthy volunteers - Stichtenoth, Dirk O.; Marhauer, Verena; Tsikas, Dimitrios; Gutzki, Frank-Mathias; Frolich, Jurgen C. (Kidney international, 2005)
Effects of specific COX-2-inhibition on renin release and renal and systemic prostanoid synthesis in healthy volunteers. The renin-angiotensin system plays a critical role in cardiovascular function, but little is known about the effects of specific cyclooxygenase 2 (COX-2) inhibition on this system in healthy humans under physiologic conditions. Twenty-one healthy female volunteers received, in a randomized, double-blind, crossover study, celecoxib 200mg twice a day, indomethacin 50mg three times a day, or placebo for 4 days and a single dose, each, on day 5. On day 5 of each treatment, the following parameters were assessed with subjects in an upright position before and after administration of 20mg furosemide intravenously: plasma renin activity (PRA), plasma aldosterone, serum and urine electrolytes, and creatinine. Index metabolites of prostanoids were analyzed by gas chromatography-tandem mass spectrometry in 24-hour urine on day 4 and in 2-hour urines before and after furosemide administration. Baseline and furosemide-stimulated PRA were reduced to a similar degree by celecoxib and indomethacin. Plasma aldosterone and urinary excretion of potassium showed changes consistent with the alteration of PRA. Urinary excretion rates of prostaglandin E2, (PGE2), 7α-hydroxy-5, 11-diketotetranor-prosta-1,16-dioic acid (PGE-M), and 2,3-dinor-thromboxane B2 (TxB2) were not reduced by celecoxib, whereas indomethacin led to a decrease of 40%, 45%, and 80%, respectively. Both active treatments inhibited urinary excretion of 2,3-dinor-6-keto-PGF1α and 6-keto-PGF1α by 60% and 40%, respectively. Renin-release in healthy humans with normal salt intake is COX-2 dependent. While COX-1 is critical for renal and systemic PGE2 production, renal prostacyclin synthesis is apparently COX-2 dependent. Finally, the previously demonstrated shift of the thromboxane-prostacyclin balance toward prothrombotic thromboxane by specific COX-2 inhibition is confirmed.